Catalytic asymmetric oxo-Diels–Alder reactions with chiral atropisomeric biphenyl diols - Yeung, Chi-Tung; Chan, Wesley Ting Kwok; Lo, Wai-Sum; Law, Ga-Lai; Wong, Wing-Tak (Beilstein Journal of Organic Chemistry, 2019)
New chiral atropisomeric biphenyl diols 3, 4 and 6 containing additional peripheral chiral centers with different steric bulkiness and/or electronic properties were synthesized. The X-ray crystal structure of 3 shows the formation of a supramolecular structure whereas that of 6, containing additional CF3 substituents, shows the formation of a monomeric structure. Diols 1–6 were found to be active organocatalysts in oxo-Diels–Alder reactions in which 2 recorded a 72% ee with trimethylacetaldehyde as a substrate.
Keywords: asymmetric organocatalysis; axial chirality; biaryls; hydrogen bond; oxo-Diels–Alder reaction

(untitled) - Jørgensen, K. A. (Angew. Chem., Int. Ed., 2000)

(untitled) - Corey, E. J. (Angew. Chem., Int. Ed., 2002)

(untitled) - Jørgensen, K. A. (Eur. J. Org. Chem., 2004)

Comprehensive Enantioselective Organocatalysis: Catalysts, Reactions, and Applications - Du, H.; Ding, K. (Diels-Alder and Hetero-Diels-Alder Reactions, 2013)

Comprehensive Organic Synthesis - Ishihara, K.; Sakakura, A. (Hetero-Diels–Alder Reactions, 2014)

(untitled) - Desimoni, G.; Faita, G.; Quadrelli, P. (Chem. Rev., 2018)

(untitled) - Núñez, M. G.; García, P.; Moro, R. F.; Díez, D. (Tetrahedron, 2010)

(untitled) - Taheri kal Koshvandi, A.; Heravi, M. M. (Tetrahedron: Asymmetry, 2017)

(untitled) - Nicolaou, K. C.; Snyder, S. A.; Montagnon, T.; Vassilikogiannakis, G. (Angew. Chem., Int. Ed., 2002)

(untitled) - Eschenbrenner-Lux, V.; Kumar, K.; Waldmann, H. (Angew. Chem., Int. Ed., 2014)

(untitled) - Chakraborty, T. K.; Tapadar, S. (Tetrahedron Lett., 2003)

(untitled) - N'Zoutani, M.-A.; Pancrazi, A.; Ardisson, J. (Synlett, 2001)

(untitled) - Audrain, H.; Jørgensen, K. A. (J. Am. Chem. Soc., 2000)

(untitled) - Yasui, K.; Tamura, Y.; Nakatani, T.; Kawada, K.; Ohtani, M. (J. Org. Chem., 1995)

(untitled) - Bednarski, M.; Danishefsky, S. (J. Am. Chem. Soc., 1983)

(untitled) - Keck, G. E.; Li, X.-Y.; Krishnamurthy, D. (J. Org. Chem., 1995)

(untitled) - Maruoka, K.; Itoh, T.; Shirasaka, T.; Yamamoto, H. (J. Am. Chem. Soc., 1988)

(untitled) - Doyle, M. P.; Phillips, I. M.; Hu, W. (J. Am. Chem. Soc., 2001)

(untitled) - Togni, A. (Organometallics, 1990)

(untitled) - Gao, Q.; Maruyama, T.; Mouri, M.; Yamamoto, H. (J. Org. Chem., 1992)

(untitled) - Ghosh, A. K.; Mathivanan, P.; Cappiello, J. (Tetrahedron Lett., 1997)

(untitled) - Yu, Z.; Liu, X.; Dong, Z.; Xie, M.; Feng, X. (Angew. Chem., Int. Ed., 2008)

(untitled) - Kezuka, S.; Mita, T.; Ohtsuki, N.; Ikeno, T.; Yamada, T. (Bull. Chem. Soc. Jpn., 2001)

(untitled) - Lin, L.; Liu, X.; Feng, X. (Synlett, 2007)

(untitled) - Fan, Q.; Lin, L.; Liu, J.; Huang, Y.; Feng, X. (Eur. J. Org. Chem., 2005)

(untitled) - Du, H.; Zhao, D.; Ding, K. (Chem. – Eur. J., 2004)

(untitled) - Huang, Y.; Unni, A. K.; Thadani, A. N.; Rawal, V. H. (Nature, 2003)

(untitled) - Unni, A. K.; Takenaka, N.; Yamamoto, H.; Rawal, V. H. (J. Am. Chem. Soc., 2005)

(untitled) - Beemelmanns, C.; Husmann, R.; Whelligan, D. K.; Özçubukçu, S.; Bolm, C. (Eur. J. Org. Chem., 2012)

(untitled) - Friberg, A.; Olsson, C.; Ek, F.; Berg, U.; Frejd, T. (Tetrahedron: Asymmetry, 2007)

(untitled) - Rajaram, S.; Sigman, M. S. (Org. Lett., 2005)

(untitled) - Jensen, K. H.; Sigman, M. S. (Angew. Chem., Int. Ed., 2007)

(untitled) - Momiyama, N.; Tabuse, H.; Terada, M. (J. Am. Chem. Soc., 2009)

(untitled) - Villano, R.; Acocella, M. R.; Massa, A.; Palombi, L.; Scettri, A. (Tetrahedron Lett., 2007)

(untitled) - Zhuang, W.; Poulsen, T. B.; Jørgensen, K. A. (Org. Biomol. Chem., 2005)

(untitled) - Goldfuss, B.; Rominger, F. (Tetrahedron, 2000)

(untitled) - Yeung, C.-T.; Yeung, H.-L.; Chan, W. T. K.; Yan, S.-C.; Tam, E. C. Y.; Wong, K.-L.; Lee, C.-S.; Wong, W.-T. (CrystEngComm, 2013)

(untitled) - Yeung, C.-T.; Chan, W. T. K.; Lo, W.-S.; Law, G.-L.; Wong, W.-T. (Molecules, 2019)

(untitled) - Gliga, A.; Goldfuss, B.; Neudörfl, J. M. (Beilstein J. Org. Chem., 2011)

(untitled) - Leven, M.; Müller, D.; Goldfuss, B. (Synlett, 2011)

(untitled) - Leven, M.; Schlörer, N. E.; Neudörfl, J. M.; Goldfuss, B. (Chem. – Eur. J., 2010)

(untitled) - Watanabe, Y.; Washio, T.; Shimada, N.; Anada, M.; Hashimoto, S. (Chem. Commun., 2009)